Holocene sedimentation in a kettle lpond breached by rising sea level on Cape Cod - Bratton, John F. (Northeast Section Meeting, Geological Society of America, 2007)
id: 1065; 1

Eutrophication and carbon sources in Chesapeake Bay over the last 2700 yr: human impacts in context - Bratton, John F.; Colman, Steven M.; Seal, Robert R. (Geochimica et Cosmochimica Acta, 2003)
To compare natural variability and trends in a developed estuary with human-influenced patterns, stable isotope ratios (δ13C and δ15N) were measured in sediments from five piston cores collected in Chesapeake Bay. Mixing of terrestrial and algal carbon sources primarily controls patterns of δ13Corg profiles, so this proxy shows changes in estuary productivity and in delivery of terrestrial carbon to the bay. Analyses of δ15N show periods when oxygen depletion allowed intense denitrification and nutrient recycling to develop in the seasonally stratified water column, in addition to recycling taking place in surficial sediments. These conditions produced 15N-enriched (heavy) nitrogen in algal biomass, and ultimately in sediment. A pronounced increasing trend in δ15N of +4‰ started in about A.D. 1750 to 1800 at all core sites, indicating greater eutrophication in the bay and summer oxygen depletion since that time. The timing of the change correlates with the advent of widespread land clearing and tillage in the watershed, and associated increases in erosion and sedimentation. Isotope data show that the region has experienced up to 13 wet-dry cycles in the last 2700 yr. Relative sea-level rise and basin infilling have produced a net freshening trend overprinted with cyclic climatic variability. Isotope data also constrain the relative position of the spring productivity maximum in Chesapeake Bay and distinguish local anomalies from sustained changes impacting large regions of the bay. This approach to reconstructing environmental history should be generally applicable to studies of other estuaries and coastal embayments impacted by watershed development.
id: 541

Birth of the modern Chesapeake Bay estuary between 7.4 and 8.2 ka and implications for global sea-level rise - Bratton, John F.; Colman, Steven M.; Thieler, E. Robert; Seal, Robert R. (Geo-Marine Letters, 2002)
Two major pulses of sea-level rise are thought to have taken place since the last glacial maximum — meltwater pulses (mwp) 1A (12 cal ka) and 1B (9.5 cal ka). Between mwp 1B and about 6 cal ka, many of the complex coastal ecosystems which ring the world’s oceans began to form. Here we report data for rhenium, carbon isotopes, total organic carbon, and fossil oysters from Chesapeake Bay which span the transition from fresh to brackish water conditions in the bay in the mid-Holocene. These data constrain sea-level change and resulting environmental change in the bay. They indicate that the transition was rapid, and that it was produced by (1) a third pulse of rapid eustatic sea-level rise, or (2) a geometry of the prehistoric Chesapeake Bay basin which predisposed it to a nonlinear response to a steadily rising sea level. Similar nonlinear changes in vulnerable coastal environments are likely to take place in the future due to polar warming, regardless of the timing or rate of sea-level rise.
id: 540